2019
DOI: 10.1515/polyeng-2019-0197
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the micro- and nanocellular foaming of polystyrene/poly(methyl methacrylate) blend composites

Abstract: Abstract Polystyrene/poly(methyl methacrylate) (PS/PMMA) blends in 80:20, 50:50, and 20:80 ratios with and without calcium carbonate nanoparticles were prepared. n-Pentane was then used to foam the samples in an autoclave. After the diffusion of n-pentane gas into the polymer matrix, the samples and the gas were simultaneously cooled to obtain the liquid n-pentane phase. Phase change to liquid prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…[34][35][36][37][38] The diffusivity and solubility of CO 2 in PMMA and PS matrices are increased by enhancement of pressure and reduction of temperature, respectively. 9,39 Jahani et al 40 investigated the foaming of PMMA/PS blends by n-pentane gas as a physical foaming agent, in the presence of calcium carbonate nanoparticles. They observed that the addition of calcium carbonate nanoparticles enhanced the morphological and mechanical properties of the final foams.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38] The diffusivity and solubility of CO 2 in PMMA and PS matrices are increased by enhancement of pressure and reduction of temperature, respectively. 9,39 Jahani et al 40 investigated the foaming of PMMA/PS blends by n-pentane gas as a physical foaming agent, in the presence of calcium carbonate nanoparticles. They observed that the addition of calcium carbonate nanoparticles enhanced the morphological and mechanical properties of the final foams.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleating agent increases the nucleation density to the values required to reduce the cell size to the nanoscale (higher than 10 13 nuclei/cm 3 ), allowing to produce nanocellular polymers. In the last years, several studies were conducted focusing on the effect of nucleating species in the fabrication of nanocellular polymers, such as nanoparticles [ 17 , 18 , 19 , 20 ] or an immiscible polymeric second phase [ 21 , 22 ]. For instance, Liu et al [ 23 ] synthesize silica nanoparticles with different surface roughness to enhance the nucleation of poly(methyl-methacrylate) PMMA.…”
Section: Introductionmentioning
confidence: 99%
“…26 Also we investigated the foaming process of PS/PMMA blends and copolymers by our designed bath system and the cellular structures of produced polymer foams were fully illustrated. 2730 Most of the models developed so far have been expressed in a form of an exponential function of either the free volume or the free volume fraction. In order to apply the models to estimating the diffusion of gas in a polymer, one must estimate the specific free volume of the polymer/gas mixture and to determine model parameters, such as the pre-exponential coefficient, an activated energy, etc.…”
Section: Introductionmentioning
confidence: 99%